mRNA expression of ezrin in gingival crevicular fluid and whole blood of gingivitis and chronic periodontitis patients - A polymerase chain reaction study - Anju Cecil; Savita Sambashivaiah; Shivaprasad Bilichodmath; Rubin S John (Wolters Kluwer Medknow Publications, 2022)
Background: A comparative analysis of protein expression of gingival crevicular fluid (GCF) obtained from healthy individuals and individuals with periodontal diseases would help to identify proteins involved in periodontal disease progression. Among the identified proteins, Moesin which is a disease-associated protein belongs to the ezrin-radixin-moesin protein family and was proved to play an important role in the recognition of oral bacteria contributing to the consequent development of inflammatory immune responses involved in periodontal disease development. Aim: The aim of the study is to quantify and compare mRNA expression levels of ezrin in GCF and whole blood of gingivitis and chronic periodontitis patients. Materials and Methods: A total of 60 patients were selected for the study and were divided into three groups as follows: Group 1 (20 participants with healthy gingiva), Group 2 (20 participants with gingivitis), and Group 3 (20 participants with chronic periodontitis). Clinical parameters such as gingival index, periodontal index, probing pocket depth, and clinical attachment level were assessed. GCF and blood samples were taken from these patients and assessed for the mRNA expression of ezrin using real-time polymerase chain reaction. Results: The expression and mean relative quantification of mRNA expression of ezrin in GCF and blood were higher for periodontitis (18.32 ± 8.398, 19.34 ± 9.487) when compared to that of gingivitis (5.34 ± 3.609, 5.48 ± 4.428) and healthy individuals (2.33 ± 0.643, 3.47 ± 1.923) and they positively correlated with the clinical parameters. Conclusion: The increased expression of ezrin can be considered as a good indicator to assess the inflammatory activity in periodontitis and gingivitis.